Peningkatan Kapasitas Pelaku Usaha melalui Pendampingan Penerapan Strategi Pemasaran Digital Berbasis Participatory Action Research (PAR) - Yanah, Nur; Mabruroh, Roichatul; Nisak, Cholifatun (LP3M IAIFA Kediri, 2025)
Marketing is a crucial aspect of business development, especially in the digital era where promotional strategies require continuous adaptation. The bottled water business managed by Pondok Pesantren Riyadus Samawi Ludoyo Kanigoro Blitar faces challenges due to limited understanding and application of digital marketing, resulting in low product recognition and suboptimal competitiveness. This community service activity focuses on strengthening the capacity of business managers in implementing relevant digital marketing strategies. Its objectives are to provide conceptual insights into digital marketing, assist in formulating promotional strategies, and encourage the application of digital marketing techniques in the operational management of the pesantren’s bottled water business. The method employed is the Participatory Action Research (PAR) approach, consisting of three stages: identifying and analyzing needs through observation, interviews, and discussions involving the service team, business managers, students, and the pesantren leadership; conducting a training session in the form of a workshop titled “Implementation of Digital Marketing Systems to Increase Bottled Water Sales” as a medium for knowledge and practice transfer; and carrying out participatory monitoring and evaluation to assess the implementation of materials and changes in marketing strategies after the activity. The results indicate an improvement in participants’ understanding of digital marketing concepts, the emergence of promotional initiatives using digital platforms, and initial changes in the marketing practices of the pesantren’s bottled water business. This approach provides a strategic foundation for developing more effective and sustainable marketing efforts.